2020
DOI: 10.1186/s12881-020-01043-9
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α − 308 G/A and IFN-γ + 874 A/T gene polymorphisms in Saudi patients with cutaneous leishmaniasis

Abstract: Background: Cutaneous leishmaniasis (CL) is well linked with immunogenetic factors. This study was undertaken to test the association of TNF-α − 308 and IFN-γ + 874 gene polymorphisms with the susceptibility of Leishmania (L) species among CL patients in central region of Saudi Arabia.Methods: This is a case-control study involved 169 Saudi subjects with different L. species and 199 healthy controls from central region of Saudi Arabia. All subjects were characterized by TNF-α − 308 G/A and IFN-γ + 874 A/T gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…For the first time in the literature, our study demonstrated a highly significant association between TNF-α 308 G/A SNP and susceptibility to CL caused by L tropica. According to the data of our study, carrying TNF-α 308 A allele, GA genotypes and GA + AA genotypes was a risk factor for developing CL (Tables 3 and 4 33 On the other hand, Ahmed et al 22 and Kamali-Sarvestani et al 25 reported a significant association between IFN-γ +874 A/T polymorphisms and CL. Controversial results were also presented in studies with VL patients.…”
Section: Ta B L Esupporting
confidence: 50%
See 4 more Smart Citations
“…For the first time in the literature, our study demonstrated a highly significant association between TNF-α 308 G/A SNP and susceptibility to CL caused by L tropica. According to the data of our study, carrying TNF-α 308 A allele, GA genotypes and GA + AA genotypes was a risk factor for developing CL (Tables 3 and 4 33 On the other hand, Ahmed et al 22 and Kamali-Sarvestani et al 25 reported a significant association between IFN-γ +874 A/T polymorphisms and CL. Controversial results were also presented in studies with VL patients.…”
Section: Ta B L Esupporting
confidence: 50%
“…Their study demonstrated that TNF‐α 308 G/A polymorphisms were significantly associated with MCL infections caused by L braziliensis 28 . Contrary results have been presented in several studies with different forms of clinical leishmaniasis caused by different Leishmania species 22,25,29‐31 …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations